2015
DOI: 10.4172/2155-9600.1000376
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Antioxidant Properties of the Diterpenes from Seeds of Phalaris canariensis

Abstract: Aims: The role of free radical reactions in disease pathology is well established, suggesting that these reactions are necessary for normal metabolism but can be detrimental to health as well acting on different levels in an oxidative sequences, the antioxidants prevents the risk of several aging related diseases including cancer, cardio vascular disorder, diabetes, neurodegenerative disorders and others. Main methods: Bioactivity-guided fractionation of a hexane extract of the seeds of P. canariensis afforded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several studies revealed phytochemical compounds that exhibit free radical scavenging activity, which was present in A. bunius leaves extract. Such compounds include unsaturated lactones, saponins, diterpenes, phenolics, and tannins (Yang, et al, 2016;Chen, et al, 2014;Perez and Ahuatzi, 2015;Daglia, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed phytochemical compounds that exhibit free radical scavenging activity, which was present in A. bunius leaves extract. Such compounds include unsaturated lactones, saponins, diterpenes, phenolics, and tannins (Yang, et al, 2016;Chen, et al, 2014;Perez and Ahuatzi, 2015;Daglia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evidence has shown that small amounts of phenolics have modulatory effects on selective intracellular signaling pathways critical for cellular functions such as proliferation and apoptosis (Ozcan, et al, 2014). Diterpenes, on the other hand, are found to be effective antioxidant by inhibiting lipid peroxidation and lipoxygenase (Perez and Ahuatzi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gramine ( 11) is a common indole alkaloid in Poaceae family and was isolated from P. arundinacea and root of P. aquatic and other gramine derivatives (12)(13)(14) were isolated from P. aquatic In addition of two oxindoles alkaloids and one furanobisindole type (20)(21)(22) were found in P. coerulescens, together with tryptamine derivatives (16-19) from P. arundinacea and P. tuberosa. Finally two other classes of alkaloids, phenethyl amine and tetrahydro-β-carboline, (15,23) were found in P. arundinacea [14][15][16][17][18][19][20][21].…”
Section: Alkaloidsmentioning
confidence: 99%
“…Abietane diterpenes were isolated from hexane fraction of P. canariensis seeds including canarien A (24), abietatrien-3bacetyl-6,19-olide (34) and abietatrien-3β-acetyl-2bol-6,19olide (35) [22,23] . Furthermore, diterpenes of pimaranes type were reported from hexane fraction of P. canariensis seeds such as canarien B (25) (32), and 19hydroxy-3β,11α-diacetylpimara-15-ene (33) [22,23].…”
Section: Diterpenesmentioning
confidence: 99%